2017
DOI: 10.1186/s12889-017-4816-4
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis mansoni incidence data in Rwanda can improve prevalence assessments, by providing high-resolution hotspot and risk factors identification

Abstract: BackgroundSchistosomiasis mansoni constitutes a significant public health problem in Rwanda. The nationwide prevalence mapping conducted in 2007–2008 revealed that prevalence per district ranges from 0 to 69.5% among school children. In response, mass drug administration campaigns were initiated. However, a few years later some additional small-scale studies revealed the existence of areas of high transmission in districts formerly classified as low endemic suggesting the need for a more accurate methodology f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Moreover, in our study socio-economic risk factors were excluded from the explanatory risk factors (including access to improved water for domestic uses, proper sanitation, wearing shoes, bush defecation behavior, etc.) 14 . Those factors are represented by qualitative (%ge) and not spatially explicit figures—result of integrated living conditions surveys extrapolated at district level (10 times + bigger than a HFSA).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in our study socio-economic risk factors were excluded from the explanatory risk factors (including access to improved water for domestic uses, proper sanitation, wearing shoes, bush defecation behavior, etc.) 14 . Those factors are represented by qualitative (%ge) and not spatially explicit figures—result of integrated living conditions surveys extrapolated at district level (10 times + bigger than a HFSA).…”
Section: Introductionmentioning
confidence: 99%
“…The use of buffers was criticized because it is based on unrealistic straight-line distances which do not account for topography, transport modes, seasonality, mobility of people, the attractiveness of facilities, the inability of sick people to walk, and documented healthcare-seeking behaviour (such as bypassing the nearest facility). Straight-line distances are unrealistic, do not account for topography, transport modes, the likelihood of living beyond the threshold, lack of updated spatial and healthcareseeking behaviour data, the inability of sick people to walk, facilities are not uniformly attractive, seasonal mobility of people, bypassing of the nearest facility, the catchment is not a function of distance only Radial buffers accounting for geographical barriers [55], enumeration [56,57] or parish boundaries and road networks [34,58] Thiessen polygon, a region incorporating all points that are closer to a given facility than any other [6,[59][60][61] All points that are closer to a given facility than any other Health facility, coarse residential location Straight-line distances are unrealistic, bypassing the nearest facility, does not account for transport modes, healthcare-seeking behaviour and other factors beyond distance, percapita utilization rate is constant within the HFCA Thiessen polygon with boundaries, travel factors, buffers, and population [62] Modelled travel time or distance based on a leastcost path model [5,13,38,[63][64][65][66][67][68][69][70][71][72] or on network analysis [73] often adjusted for facility capacity [74], population [75], Thiessen polygon [76], boundary [77,78] [71] combined with patient address [88] and gravity models [89] considers interaction between supply and demand Facility, urban residence, travel factors, population, capa...…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was reported that certain species of vegetation and other biota in snails’ habitat can affect transmission to man. It was, thus, shown that water lilies 37 and rice 38 affect snail abundance and support increased cercarial numbers in the corresponding sites. On the other hand, attachment of rotifers to snails inhibits development of schistosomes within them and reduces the viability of cercariae.…”
Section: Snail-to-man Transmission Capacitymentioning
confidence: 99%